The Effect of Sensory Play Classes on Emotional Regulation in Children Aged 4 to 5 Years - Aning Kuni Irodatan; Nurhafit Kurniawan; Ahmad Afandi (Electronic Journal of Education, Social Economics and Technology, 2025)
The purpose of this study was to determine whether or not there was an effect of sensory play classes on the emotional regulation of children aged 4–5 years. This study was a quantitative study with a quasi-experimental approach (quasi-experimental research) that aimed to determine the effect of sensory play classes on the emotional regulation of children aged 4–5 years. This study used a non-equivalent control group design, in which there were two groups, namely the experimental group (taking sensory play classes) and the control group (taking regular learning). The results of the study showed that based on the pretest and posttest data, as well as the statistical tests that had been carried out, it can be concluded that after the treatment in the form of sensory play classes was given to the experimental group for eight meetings, there was a significant increase in emotional regulation scores. The posttest results showed a fairly large difference in scores between the experimental group (average = 65.89) and the control group (average = 50.13), with significant t-test results (p = 0.000 0.05). The normality and homogeneity tests indicated that the data from both groups met the requirements of the parametric test, with normal data distribution and homogeneous variance. Thus, it can be concluded that sensory play classes have a significant influence on improving emotional regulation in children aged 4–5 years. Children become more able to recognize, control, and express their emotions in a more positive way after participating in sensory play sessions.